Undifferentiated Embryonal Sarcoma of the Liver: Report of 2 Cases - Pacharn, Preeyacha (Siriraj Medical Journal, 2016)
Undifferentiated embryonal sarcoma (UES), also known as undifferentiated liver sarcoma (ULS) is a rare, primary malignant neoplasm of the liver, affecting mostly pediatrics and young adults. Clinical symptoms and plain radiographs are usually nonspecific. Sonographic, CT and/or MRI findings are more sensitive and can help to differentiate this tumor from other conditions. The differential diagnosis includes hydatid cyst, cystic hepatoblastoma, mesenchymal harmatoma and biliary neoplasm. In this illustration, we would like to report 2 patients with UES who were 9 year-old and 13 year-old girls. Radiologic and pathologic imaging will be discussed.